Adaptation of Slang and Western Culture in Recent Bangladeshi Dramas and Web Series: Cultural Degradation or Trend? - Akter, Fahmida (Feni University Journal, 2026)
Slang words are considered informal expressions or uses of informal words. The use of slang is an informal linguistic behavior of a particular human being that varies from person to person. In Bangladesh, dramas and web series are considered a great source of entertainment for everyone. Usually, dramas and web series represent good content acceptable to all. These two categories are considered to be family-oriented media creations. However, in recent times, these two categories have been influenced by the cultures of other countries. More specifically, dramas and web series are being influenced by Western culture. While adopting Western culture, dramas and web series are getting their original glory or roots. Dramas and web series producers have recently rapidly adopted slang and other concepts. Three selected dramas and web series of Bangladesh, “Bachelor Point, Girls Squad, and August 14,” represent how to adopt slang from Western to Bangladeshi culture. These three media pieces examine the way and ratio of Western culture and slang in Bangladeshi culture and how it influences the people of Bangladesh. This study investigates the reasons behind adopting slang and the characteristics of Western culture. It also examines the rationale for randomly using slang and Western culture in the three selected media pieces. The current study depicts how all the characters are randomly adopting the use of slang and the tradition of Western culture. It shows that the adaptation of slang and Western culture is ruining the tradition and personhood of a particular person, as they are imitating things that are not parts of Bangladeshi culture. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (235-247)